Nutrient depletion and particulate matter near the iceedge in the Weddell Sea - Pérez, Fiz F.; Figueiras, F. G.; Ríos, Aida F. (Inter Research, 1994)
11 pages, 6 figures, 4 tables. The region between Elephant Island the South Orkney Islands (53.5º S, 46.5º W) was occupied by Winter Weddell Sea water and a thick layer of summer and surface modified Weddell Water. High correlations between nutrients (nitrate, total inorganic carbon, silicate) and oxygen with salinity were found in the upper 150m near the ice-edge. Nutrient depletion was calculated and correlated with the melting ice processes. When 1 m of ice melts, the average amount of total carbonate and nutrients removed is equivalenyt to a production of 33 g C m(-2) yr(-1). Increase of oxygen were detected with high rates of nutrient and carbon depletion. However, significant oxygen losses in the melting water body were estimated from the conservative `NO´parameter. The amount of nutrients removed during pack-ice melting was about 3 times higher than that taken up in the water column. Analyses of particulate material in the ice samples showed similar C:N ratios to those estimated by the decrease of nutrients in the water column. This study was carried out as a collaborative project between the Institute of ecology (Polish Academy of Sciences) and CSIC, and was supported by project numbver MAR88-245 of Comision Interministerial de Ciencia y Tecnologia. Peer reviewed